Gender-Based Violence ‘Matters’: An Analysis of Conflicting Frames of Violence in South African Media - Ndlovu, James; Mandiyanike, Marcia (Social sciences (Basel), 2025)
Gender-based violence (GBV) in South Africa continues to be a critical issue affecting the society. It is deeply entrenched within patriarchal structures shaped by historical injustices of colonialism and apartheid. Despite several legislative and policy initiatives aimed at addressing the scourge of GBV, media representations often perpetuate traditional gender stereotypes and biased narratives. Evidence from previous studies highlights the role of media in reinforcing gender inequalities by frequently sensationalizing violence and victim-blaming, thereby marginalizing the experiences of women. This paper contributes to ongoing debates on media framing by critically examining contemporary South African media narratives on GBV. The study will employ a framing analysis approach to scrutinize the key frames utilized by South African media in reporting GBV, drawing from significant scholarly works and news articles from IOL on GBV. Three empirical questions guide this study: (i) What frames are prevalent in media coverage of GBV in post-pandemic South Africa? (ii) Are there identifiable biases within these media narratives? (iii) How do media representations either reinforce or challenge entrenched patriarchal discourses? Analysis of selected news articles reveals persistent media practices that reinforce gender-biased stereotypes and diminish women’s agency and lived realities. Despite notable examples of counter-discourses emerging through digital activism, traditional media channels often undermine progressive efforts, perpetuating the perception that GBV remains inadequately addressed. This paper underscores the urgent need for more nuanced and transformative media practices that challenge systemic gender inequalities and promote genuine societal change in South Africa’s evolving post-apartheid context. The paper explores the growing GBV matters in the post-apartheid South Africa as presented in the media and argues that GBV matters. The paper pays particular attention to the inclusion and framing of women’s perspectives in the coverage of GBV in South Africa.